C-type natriuretic peptide plasma levels and whole blood mRNA expression show different trends in adolescents with different degree of endothelial dysfunction - Del Ry, Silvia; Cabiati, Manuela; Bianchi, Vanessa; Randazzo, Emioli; Peroni, Diego; Clerico, Aldo; Federico, Giovanni (Peptides (New York, N.Y. : 1980), 2020)
•C-type natriuretic peptide (CNP) is an endogenous adipogenesis regulator.•CNP plasma levels and mRNA were evaluated, for the first time, in whole blood.•Normal and obese adolescents were enrolled.•A different trend was observed for CNP plasma levels and its expression.•Interesting area for new therapies. C-type natriuretic peptide (CNP) is an endogenous adipogenesis regulator whose plasma levels in childhood are known, while no data are available on its expression. Our aim was to evaluate both CNP plasma levels and CNP system expression in whole blood obtained from normal-weight (N, n = 24) and obese (O, n = 16) adolescents (age:13.5 ± 0.4 years). Endothelial function was assessed measuring reactive hyperemia index (RHI). CNP plasma levels, evaluated with specific RIA, resulted significantly lower in O than in N (6.1 ± 0.8 vs.15.2 ± 1.3 pg/mL; p < 0.0001), while CNP/NPR-B/NPR-C mRNA, measured by Real-Time PCR, resulted similar in N (4.1 ± 1.7; 5.0 ± 1.6; 2.2 ± 0.9) and in O (4.3 ± 1.6; 3.5 ± 1.1; 2.3 ± 0.8). RHI was significantly lower in O than in N (1.4 ± 0.08 vs.2.1 ± 0.04, p < 0.0001). Dividing all subjects according to the RHI median value, irrespective of the presence or absence of obesity (Group 1 > 1.9, n = 23, Group 2 < 1.9, n = 17), CNP plasma concentrations resulted significantly (p = 0.014) higher in Group 1 (14.6 ± 1.6) than in Group 2 (7.5 ± 1.0), showing a significant correlation with RHI (p = 0.0026), while CNP mRNA expression was, surprisingly, higher in Group 2 (7.0 ± 2.3) than in Group 1 (1.8 ± 0.4; p = 0.02). NPR-B mRNA resulted similar in both Groups (4.3 ± 1.6; 4.7 ± 1.3) and NPR-C significantly higher in Group 2 (p = 0.02). Our data suggest different trends between CNP plasma levels and expression, assessed for the first time in whole blood, that could reflect changes occurring both at CNP transcriptional level in activated leukocytes due to inflammation, and at circulating levels, due to CNP paracrine/autocrine activities. This could represent an interesting area for new therapies able to modulate endothelial dysfunction.